Low prevalence of Helicobacter pylori in inflammatory bowel disease: association with sulphasalazine. Issue 10 (October 1994) - el-Omar, E; Penman, I; Cruikshank, G; Dover, S; Banerjee, S; Williams, C; McColl, K E
Abstract : The prevalence of IgG antibodies to Helicobacter pylori was examined in 110 patients with inflammatory bowel disease (IBD) (63 ulcerative colitis, 47 Crohn's disease) and compared with 100 age and sex matched control patients. The overall prevalence of H pylori seropositivity in the IBD patients was 22%, which was significantly less than that of 52% in the controls (p < 0.002). There was no difference in prevalence between ulcerative colitis and Crohn's patients. The low seropositivity in the IBD patients resulted from a very low prevalence of 10% in those currently receiving sulphasalazine (n = 40) and similarly low prevalence of 7% in those previously receiving sulphasalazine (n = 30). In those receiving olsalazine or mesalazine and who had never had sulphasalazine, the prevalence of seropositivity was 45%. Further studies using 14C urea breath test and microscopy of antral biopsy specimens confirmed that the negative serology in patients receiving sulphasalazine resulted from absence of the infection rather than absence of humoral immune response to it. In six control patients with H pylori infection, a two week course of sulphasalazine (500 mg four times daily) only caused slight suppression of the 14C urea breath test. In vitro studies failed to show any direct antibacterial effect of sulphasalazine on H pylori. These findings indicate that longterm treatment with sulphasalazine leads to eradication of H pylori infection and that this does not result from a direct antibacterial effect. It may be caused by the drug treating the gastritis and thereby depriving the bacterium of essential nutrients exuded by the inflamed mucosa.